Mangrove distribution to support biodiversity management in Teluk Bintuni District, West Papua, Indonesia - PETRUS KASIHIW; RONI BAWOLE; JONNI MARWA; AGUSTINUS MURDJOKO; ALEXANDER WIHYAWARI; YUNO HEIPON; REINARDUS LIBORIUS CABUY; NITHANEL MIKAEL HENDRIK BENU; FRANCINE HEMATANG; NICOLAUS Y. LEFTUNGUN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Kasihiw P, Bawole R, Marwa J, Murdjoko A, Wihyawari A, Heipon Y, Cabuy RL, Benu NMH, Hematang F, Leftungun NY. 2024. Mangrove distribution to support biodiversity management in Teluk Bintuni District, West Papua, Indonesia. Biodiversitas 25: 644-653. Mangroves play an important role in coastal ecosystems, but the areas of mangroves are decreasing globally. Understanding the ecological and geographical distribution of mangroves will be useful to develop sustainable management and policy. Thus, this study aimed to analyze the ecological and geographical distribution of mangroves in Teluk Bintuni, West Papua, Indonesia. The distribution of mangroves was investigated to see the relationships between elevation and the number of individual mangroves at the family level. Vegetation data were collected by setting 180 circular plots and geographical data were obtained from secondary sources. Our study revealed that Rhizophoraceae family was found in all plots with 97.78% presence, whereas Acanthaceae and Meliaceae families were found in half of the plots with 65% and 60.56% presence, respectively. Lythraceae, Primulaceae, Malvaceae, and Arecaceae were only found in 15% of the plots. Elevation affected significantly the presence of mangroves which there mainly occurred in elevation between 10-30 m asl, while they were lower in below 10 m asl and above 30 m asl. Species belonging to Acanthaceae and Lythraceae, such as those from the genera of Avicennia and Sonneratia, were found more abundant in the low elevation (seaward zone) than in the higher elevation (landward zone). In contrast, species belonging to Meliaceae and Rhizophoraceae were more abundant in the landward zone with the presence of genera Xylocarpus, Bruguiera, Ceriops, and Rhizophora. The distribution of Arecaceae, Malvaceae, and Primulaceae did not show a significant pattern where they appeared randomly in mangrove forests. Geographically, 12.43% area of Teluk Bintuni District was mangroves which mainly occurred in the eastern and southern parts. Based on forest status, 2.23%, 35.60%, 10.46%, and 51.71% of mangroves in Teluk Bintuni occur in non-forestry use areas (Area Penggunaan Lain/APL), conservation forest (Hutan Konservasi) in the form of nature reserve, protected forest (Hutan Lindung), and production forest (Hutan Produksi), respectively. As the mangrove ecosystem has been part of local people, the specific management to support biodiversity in mangrove forests must be put officially in the development program.